2017
DOI: 10.1111/jgs.15016
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Potentially Inappropriate Medication Use at Nursing Home Transition

Abstract: Many residents with cognitive impairment or dementia enter nursing homes on PIMs. PIMs are more likely to be started in frail individuals following admission. Interventions to support deprescribing of PIMs should be implemented targeting frail individuals during the transition to nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 48 publications
(92 reference statements)
7
63
2
2
Order By: Relevance
“…Harrison et al depicted similar findings in a cross-sectional study with a significant association between higher DBI and poorer QOL, as well as increasing PIMs and poorer QOL [36]. This can be explained by the nature of inappropriate medication use, which commonly leads to adverse outcomes that affects participants' morbidity and QOL [37,38]. In contrast, there was a statistically significant and negative association between medication inappropriateness and dependency.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Harrison et al depicted similar findings in a cross-sectional study with a significant association between higher DBI and poorer QOL, as well as increasing PIMs and poorer QOL [36]. This can be explained by the nature of inappropriate medication use, which commonly leads to adverse outcomes that affects participants' morbidity and QOL [37,38]. In contrast, there was a statistically significant and negative association between medication inappropriateness and dependency.…”
Section: Discussionmentioning
confidence: 67%
“…This, however, contradicts several studies that have reported a positive correlation between both parameters. This could be due to the setting of this study as the participants were non-institutionalized individuals with better health status [38,39] than those in settings such as aged-care facilities, nursing homes and retirements villages [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…2,12,13 Assessment items from the RAI-MDS 2.0 provided measures of clinical diagnoses, functional status and cognitive performance; they were also used to calculate a validated measure of resident frailty. 14,15 This index of frailty covers many domains of health and is calculated as the proportion of accumulated to potential health deficits (from 72 RAI-MDS items) whereby those with greater than 30% of potential deficits are defined as frail. We used the Johns Hopkins Adjusted Clinical Groups® case-mix system (version 10.0) to compute the number of Aggregated Diagnosis Groups in the past 2 years as a general measure of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…We used the RAI-MDS 2.0 data to identify assessments with a concurrent diagnosis of Alzheimer disease or other dementia, and liver disease or renal failure. 23 We also used assessment items from the RAI-MDS 2.0 to compute a validated measure of resident frailty, 24,25 which included 72 deficits covering multiple domains of health (disease diagnoses, functional status, psychosocial well-being, cognition and communication). In accordance with previous work, [24][25][26] we defined residents with more than 30% of potential deficits as frail.…”
Section: Resident Characteristicsmentioning
confidence: 99%
“…23 We also used assessment items from the RAI-MDS 2.0 to compute a validated measure of resident frailty, 24,25 which included 72 deficits covering multiple domains of health (disease diagnoses, functional status, psychosocial well-being, cognition and communication). In accordance with previous work, [24][25][26] we defined residents with more than 30% of potential deficits as frail. We used a measure of pain frequency in the RAI-MDS 2.0 to identify residents who experienced daily pain, less than daily pain or no pain in the 7 days before assessment.…”
Section: Resident Characteristicsmentioning
confidence: 99%